2005
DOI: 10.2190/06m5-huk3-02al-r993
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Evaluation of Educational Intranets

Abstract: A major determinant of the success of educational intranet sites is their usability. In addition to measures of task performance and navigation behavior, psychometric instruments are used to evaluate usability and the quality of human-computer interaction more generally. However, there is a lack of validated instruments for the evaluation of sites. The aim of the present study was to establish the psychometric properties of scales for measuring the quality of interaction with educational intranets. In two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…These systems include Virtual Learning Environments (VLEs), such as Blackboard TM and WebCT TM , and library information systems-especially academic-library websites. Because intranet and externally accessible websites increasingly become the interface to information for learning materials and communication, usability 1 becomes of paramount importance for progression and retention of students (van Schaik & Ling, 2005). However, usability is not sufficient and large potential gains in effectiveness and performance will not be realized if users are not willing to use information systems in general (Davis, 1993) and educational websites in particular; therefore, acceptance 2 is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…These systems include Virtual Learning Environments (VLEs), such as Blackboard TM and WebCT TM , and library information systems-especially academic-library websites. Because intranet and externally accessible websites increasingly become the interface to information for learning materials and communication, usability 1 becomes of paramount importance for progression and retention of students (van Schaik & Ling, 2005). However, usability is not sufficient and large potential gains in effectiveness and performance will not be realized if users are not willing to use information systems in general (Davis, 1993) and educational websites in particular; therefore, acceptance 2 is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, for single-item layout average variance extracted (AVE) for the Flow Subscale Concentration was significantly higher than whole-form layout. Moreover, for Concentration and 7 In addition to the flow scale (see above), the disorientation scale (Ahuja & Webster, 2001;van Schaik & Ling, 2003, 2005a, 2005b, 2007, 2012a) and the GEFT (Witkin et al, 1971(Witkin et al, /2002 have previously been shown to have good psychometric properties. The GEFT scale scores range from 0 to 18.…”
Section: Psychometric Analysismentioning
confidence: 99%